Efficacy of complex neuroprotection in glaucomatous optic neuropathy (Ukrainian Journal of Ophthalmology, 2026)
Background. The problem of glaucomatous optic neuropathy is not solved regardless the fact that intraocular pressure is stabilized. To manage the glaucomatous process, effective neuroprotection of the ganglion cells is required. The purpose of the paper was to study the efficacy of complex neuroprotection in patients with glaucomatous optic neuropathy using sequential laser radiation of the papillomacular bundle followed by a six-month vitamin and antioxidant supplement therapy.   Material and Methods. We followed up 27 patients (43 eyes) with advanced open angle glaucoma, verified glaucomatous optic neuropathy (GON), and stabilized intraocular pressure (IOP). The patients’ age averaged 63.8 (SD; 6.8). A treatment course included 10 every-day sessions of laser stimulation (LS) using a SM-4.3 unit (wavelength, 650 nm; irradiance, 0.4 mW/cm2; treatment timing, 240 s on the papillomacular bundle) and additional directed laser radiation to the optic disc (OD) using a 90 D lens (treatment timing, 60 s). Thereafter, patients received a vitamin supplement with 1 mg resveratrol: one capsule daily for 6 months.Results. A combined treatment including LS of the optic nerve and the papillomacular bundle followed by a six-month vitamin and antioxidant supplement therapy with resveratrol in patients with glaucomatous optical neuropathy made it possible to increase visual acuity from 0.65 to 0.82 (by 26%), to increase visual system sensitivity with phosphene current threshold decreased from 84.9 μA to 76 μA (by 10%), to improve ocular blood circulation from 2.4 to 2.6‰ (by 8%),  to decrease vasospasm from 26.7 to 21.8% (by 18%), significantly increase overall retinal light sensitivity from 1395.0 to 1709.0 dB (by 23%), and to stabilize the glaucomatous process within six months. Analyzing the data obtained after a neuroprotective LS course with a subsequent vitamin antioxidant supplementation therapy with reseratrol (1 mg) revealed an apparent correlation between an increase in overall light sensitivity of the retina and an increase in the blood circulation in the eye (rs=0.71, р
Keywords: glaucomatous optic neuropathy; neuroprotection; laser stimulation; nutrition therapy